2007
DOI: 10.1051/0004-6361:20077196
|View full text |Cite
|
Sign up to set email alerts
|

Prominence and quiet-Sun plasma parameters derived from FUV spectral emission

Abstract: Context.A solar prominence and the quiet-Sun (QS) were observed with SOHO/SUMER in October 1999. With this dataset we built the first comprehensive UV spectral atlas in the range 800-1250 Å for a prominence, thus complementing the existing reference atlases for the QS. Aims. This is a detailed study based on the information in this atlas, with the aim of deriving the plasma parameters in two distinct regions. The large amount of information available allows us to establish these parameters with lower uncertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(101 citation statements)
references
References 37 publications
5
95
1
Order By: Relevance
“…The values of these input parameters correspond well to the characteristic quiescent prominence values and lead to highly realistic prominence finestructure models. This can be complemented by the derivation of the electron density for the June 8, 2004 prominence using the line-ratio technique of the C iii 977 Å and 1174.9 Å lines (Cirigliano et al 2004;Parenti & Vial 2007), which gives a value of electron density equal to 3.08 × 10 8 cm −3 at the C iii formation temperature of about 70 000 K. This leads to a value of the gas pressure at this temperature approximately equal to 0.006 dyn cm −2 , which corresponds to the p tr values of the selected models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The values of these input parameters correspond well to the characteristic quiescent prominence values and lead to highly realistic prominence finestructure models. This can be complemented by the derivation of the electron density for the June 8, 2004 prominence using the line-ratio technique of the C iii 977 Å and 1174.9 Å lines (Cirigliano et al 2004;Parenti & Vial 2007), which gives a value of electron density equal to 3.08 × 10 8 cm −3 at the C iii formation temperature of about 70 000 K. This leads to a value of the gas pressure at this temperature approximately equal to 0.006 dyn cm −2 , which corresponds to the p tr values of the selected models.…”
Section: Discussionmentioning
confidence: 99%
“…Thus for the June 8 prominence, the most reliable part of the derived DEM curve is the low-temperature portion lying below 10 5 K, where the value of the minimum temperature of the DEM curve is constrained by several C ii and N ii lines. The set of available observations of the studied prominence does not allow the use of cooler lines such as those used by Parenti & Vial (2007) due to their very low signal-to-noise ratios. Parenti & Vial (2007) used the SoHO/SUMER spectral atlas obtained by Parenti et al (2004Parenti et al ( , 2005 to derive the DEM for a quiescent prominence observed in 1999, where cooler lines such as Si ii were present.…”
Section: Dem Derived From Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schmahl & Orrall 1986;Wiik et al 1993;Parenti & Vial 2007;Parenti et al 2012), but none have used EIS data for this analysis. To our knowledge, no DEMs of solar tornadoes have been published at the time of writing.…”
Section: Emission Measure Distributionmentioning
confidence: 99%
“…The AIA data are provided courtesy of NASA/SDO and the AIA science team. The authors thank S. Parenti for providing the data for the DEM published in Parenti & Vial (2007), and I. Hannah for providing valuable information on analysing the DEMs provided by the Hannah & Kontar (2012) code and the use of uncertainties in this code.…”
mentioning
confidence: 99%